2005
DOI: 10.1111/j.1447-073x.2005.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell fate determination regulated by a transcriptional signal network in the developing mouse brain

Abstract: Development of the nervous system is governed by multistep processes in which neurons, astrocytes and oligodendrocytes are produced from common neural stem cells. Differentiation of stem cells into these three types of neural cells is directed, in part, by cell-external cues, such as cytokines. We have examined the effects of astrocyte-inducing cytokines, leukemia inhibitory factor (LIF) and bone morphogenetic protein (BMP) 2 on mouse telencephalic neuroepithelial cells. We found that simultaneous treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…Cyclin D1 involvement in the regulation of transcription may be particularly important for differentiation decisions during embryonic development. For example STAT3 plays a crucial role in signaling during brain development (Fukuda and Taga, 2005), whereas Beta2/NeuroD was shown to control neurogenesis (Liu et al, 2000;Del Turco et al, 2004) and pancreatic development (Habener et al, 2005). Interestingly, it was shown that the lack of cyclin D1 or cyclin D2 compromises cerebellar development (Huard et al, 1999;Pogoriler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 involvement in the regulation of transcription may be particularly important for differentiation decisions during embryonic development. For example STAT3 plays a crucial role in signaling during brain development (Fukuda and Taga, 2005), whereas Beta2/NeuroD was shown to control neurogenesis (Liu et al, 2000;Del Turco et al, 2004) and pancreatic development (Habener et al, 2005). Interestingly, it was shown that the lack of cyclin D1 or cyclin D2 compromises cerebellar development (Huard et al, 1999;Pogoriler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs), members of the TGFβ family of signaling molecules, have numerous functions in nervous system development (for reviews see (Chen et al, 2004;Fukuda and Taga, 2005). Several BMP proteins expressed in roof plate regulate the specification of dorsal neuronal cell types (Panchision et al, 2001;Timmer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fate commitment of stem cells into neuronal lineages is determined by regulation of a host of neuron-specific transcription factors and neuronal noncoding RNA expression [45][46][47]. Imaging methods using neuronal reporters or a neuronal miRNA-targeted reporter system allow us to monitor neuronal differentiation using single specific target molecules.…”
Section: Requisites Of Multiplex Imagingmentioning
confidence: 99%